Quality of life assessment after acute myocardial infarction - Bruno Henrique Fiorin; Rita Simone Lopes Moreira; Andressa Bolsoni Lopes; Walckiria Garcia Romero Sipolatti; Lorena Barros Furieri; Mirian Fioresi; Bráulio Luna Filho (Universidade Federal do Ceará, 2020)
Objective: to evaluate the quality of life after acute myocardial infarction, highlighting the differences by sex. Methods: analytical, observational study with 273 patients. For collection, a multidimensional assessment instrument was used for heart attacks. Data collected in a cardiology referral hospital, in which the t Student test was applied for analysis. Results: the majority were male (67.0%),with a mean age of 63.6 years, with a family history of heart attack (64.5%). The average quality of life score was 0.45,with 1.00 being the worst score. Dependence (0.82) and physical activity (0.50) were the worst assessed domains; and side effects (0.27) and diet (0.36), the best. The female gender had the worst averages (0.52, p<0.05), with emphasis on physical activity (0.58), emotion (0.49) and insecurity (0.44). Conclusion: impairments in quality of life were found after myocardial infarction, in which the dependency domain was the most compromised. The female sex had worse scores.